X-ray study of a sample of FR0 radio galaxies: unveiling the nature of the central engine. Issue 4 (3rd March 2018) - Torresi, E; Grandi, P; Capetti, A; Baldi, R D; Giovannini, G
Abstract: Fanaroff–Riley type 0 radio galaxies (FR0s) are compact radio sources that represent the bulk of the radio-loud active galactic nuclei (AGN) population, but they are still poorly understood. Pilot studies on these sources have been already performed at radio and optical wavelengths: here we present the first X-ray study of a sample of 19 FR0 radio galaxies selected from the Sloan Digital Sky Survey/NRAO VLA Sky Survey/Faint Images of the Radio Sky at Twenty-cm sample of Best & Heckman, with redshift ≤0.15, radio size ≤10 kpc, and optically classified as low-excitation galaxies. The X-ray spectra are modelled with a power-law component absorbed by Galactic column density with, in some cases, a contribution from thermal extended gas. The X-ray photons are likely produced by the jet as attested by the observed correlation between X-ray (2–10 keV) and radio (5 GHz) luminosities, similar to Fanaroff–Riley type I radio galaxies (FRIs). The estimated Eddington-scaled luminosities indicate a low accretion rate. Overall, we find that the X-ray properties of FR0s are indistinguishable from those of FRIs, thus adding another similarity between AGN associated with compact and extended radio sources. A comparison between FR0s and low-luminosity BL Lacs rules out important beaming effects in the X-ray emission of the compact radio galaxies. FR0s have different X-ray properties with respect to young radio sources (e.g. gigahertz-peaked spectrum/compact steep spectrum sources), generally characterized by higher X-ray luminosities and more complex spectra. In conclusion, the paucity of extended radio emission in FR0s is probably related to the intrinsic properties of their jets that prevent the formation of extended structures, and/or to intermittent activity of their engines.